2012
DOI: 10.3109/07435800.2012.710696
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of TSH Circadian Variability in Patients with Hypothyroidism

Abstract: The time of blood sampling has an important role in the interpretation of TSH levels. Moreover, the high TSH circadian variability should be considered in discussions about the narrowing of its reference range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 6 publications
0
9
0
5
Order By: Relevance
“…In addition, it has been reported that the night shift work positively correlates with the risk of developing subclinical hypothyroidism. Moreover, the duration of night working, the higher the risk (Sviridonova et al 2013). Indeed, the most sensitive and reliable screening test for detection of subclinical hypothyroidism is the serum TSH assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been reported that the night shift work positively correlates with the risk of developing subclinical hypothyroidism. Moreover, the duration of night working, the higher the risk (Sviridonova et al 2013). Indeed, the most sensitive and reliable screening test for detection of subclinical hypothyroidism is the serum TSH assay.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the most sensitive and reliable screening test for detection of subclinical hypothyroidism is the serum TSH assay. It is estimated that 4-15% of the general population have subclinical hypothyroidism (Sviridonova et al 2013). The prevalence rate increases to 25-50% in the case of presence of anti-thyroid peroxidase autoantibodies (anti-TPO).…”
Section: Discussionmentioning
confidence: 99%
“…Манифестный гипотиреоз характеризуется раз витием негативных сердечно сосудистых и метабо лических эффектов, включая изменения липидного профиля, дисфункцию миокарда и эндотелия, нару шения гематологических показателей. В то же время данные о наличии и выраженности аналогичных сдвигов при субклиническом гипотиреозе (СГ) оста ются противоречивыми [1,2,4,[5][6][7][8][13][14][15][16]. Неод нозначные результаты могут отчасти объясняться неоднородностью обследованного контингента по концентрации тиреотропного гормона (ТТГ) и дру гим показателям (возраст, пол, наличие сопутствую щей сердечно сосудистой патологии и др.…”
Section: Introductionunclassified
“…Дуже цікавими є дані щодо обстеження пацієнтів з діагнозом гіпотиреозу, у яких рівень ТТГ визначався зранку (08:00-09:00) і в другій половині дня (14:00-16:00) [2]. Воно підтверджує добові коливання гормону від 5,83 мМО/л зранку до 3,79 мМО/л після обіду.…”
Section: тиреотропний гормон: важливі фактори впливу які потрібно врunclassified